A New-Open-Economy Macro Model for Fiscal Policy Evaluation - Muir, Dirk (IMF Working Papers; Working Paper ;, 2006)
We develop a New-Open-Economy-Macro model in which Ricardian equivalence does not hold because of (i) distortionary labor and corporate income taxation; (ii) limited asset market participation; and (iii) because the overlapping-generations structure results in a disconnect between current and future generations. We consider a permanent increase in government debt following a cut in labor or corporate income taxes in a small and large open economy. We analyze the sensitivity of the results to the key structural parameters of the model and argue that under plausible assumptions there will be significant crowding-out effects associated with permanent increases in government debt.